2016
DOI: 10.1016/j.cub.2016.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-Binding Protein Controls Microtubule Dynamics and Cargo Trafficking by Regulating Kinesin Motor Activity

Abstract: Kinesin motor proteins play a fundamental role for normal neuronal development by controlling intracellular cargo transport and microtubule (MT) cytoskeleton organization. Regulating kinesin activity is important to ensure their proper functioning, and their misregulation often leads to severe human neurological disorders. Homozygous nonsense mutations in kinesin-binding protein (KBP)/KIAA1279 cause the neurological disorder Goldberg-Shprintzen syndrome (GOSHS), which is characterized by intellectual disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
123
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(148 citation statements)
references
References 44 publications
18
123
1
6
Order By: Relevance
“…The high anterograde velocities (v max ϭ 2.4 m/s) measured for egressing parti- cles provide biophysical support for data from previous proteomics studies (8), indicating that the fast kinesin-3 motor Kif1A (26,27) is responsible for PRV egress. Nevertheless, the velocity profile shows a plateau rather than a single peak.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The high anterograde velocities (v max ϭ 2.4 m/s) measured for egressing parti- cles provide biophysical support for data from previous proteomics studies (8), indicating that the fast kinesin-3 motor Kif1A (26,27) is responsible for PRV egress. Nevertheless, the velocity profile shows a plateau rather than a single peak.…”
Section: Discussionsupporting
confidence: 74%
“…This wide distribution of observed velocities suggested that particles encounter heterogeneity in microtubule motors, motor regulatory factors, or the local axonal environment during anterograde axonal transport. The higher velocities observed were clearly distinct from those expected for kinesin-1 motors but consistent with motility driven by kinesin-3 (Kif1A), either alone or in combination with other kinesin motors (26,27). The retrograde velocity distribution during egress lacked a distinct peak but could be fitted to an overall decay trend (Fig.…”
Section: Fig 2 Pk15-mng-vp26 Cells Produce Dual-color Prv180g (A) Tisupporting
confidence: 73%
See 1 more Smart Citation
“…ensconsin and DCLK1), however, promote recruitment and activation of kinesins on specific populations of microtubules (Sung et al, 2008;Lipka et al, 2016). Finally, KBPs can modulate kinesin activity, as shown for the inactivation of the motor domains of the kinesin-3 KIF1A and kinesin-8 KIF18A by the protein KBP (also known as KIF1BP and KIAA1279) (Kevenaar et al, 2016). It remains to be determined how all of these factors influence the ability of different kinesins to mediate different patterns of lysosome movement.…”
Section: Anterograde Transportmentioning
confidence: 99%
“…Interestingly, the presence of BICD2 increases the force generation and processivity of dynein/dynactin [127,128], demonstrating that these cargo adapter proteins regulate motor activity and could act as switches to control transport directionality within a complex containing two opposing motors. Other control mechanisms could come from accessory proteins such as kinesin binding protein (KBP), which has been shown to stimulate KIF1B, but inhibit KIF1A mediated bidirec tional transport [28,129]. If the activity of such regulato ry proteins were spatially controlled, this would enable directional switching of transport complexes in the pres ence of opposing motors.…”
Section: Cooperation Of Motorsmentioning
confidence: 99%